Potentiality of the Usage of Compressed Natural Gas for Competitiveness in Service Delivery Industries - Jamil, Gazi Mohammad Hasan; Hasan, Fuad (School of Business and Management Institut Teknologi Bandung, 2014)
Abstract. With the rising costs of gasoline, many vehicle owners are looking for alternatives of it. Compressed natural gas (CNG) has been tested for this very purpose in some countries and found as a better alternative so far. CNG comes from country’s natural resources and it is clean and less costly to use. This paper is mainly an analysis of the potential benefits of using natural gas as a transportation fuel by the service delivery industries. It will examine CNG’s potential contribution in reducing delivery and vehicle maintenance cost, saving money in the long run projects, improving fuel efficiency, enhancing physical safety and assuring environment friendly emissions of carbon monoxide or reactive gases for the service delivery industries.Keywords: Compressed natural gas (CNG), Service Delivery, Fossil fuel, Global warming, Competitiveness